2022
DOI: 10.21203/rs.3.rs-2028511/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Social Capital and Social Environmental Factors on Mental Health and Flourishing: The Experiences of Migrants in France

Abstract: Background There is growing interest on how social capital and related social environmental factors impact overall population health and well-being. The nature of migrants’ social environment changes once they migrate to a new context and these changes influence their mental health and well-being. However, there is limited scholarship on how these social environmental factors impact the mental health, well-being, and capacity to flourish of migrant populations. Methods The aim of the study, therefore, was to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…We also found that high levels of trust and solidarity were positively associated with quality of life with in our sample. Findings that the refugees depicted high levels of social capital are in line with a study, which found that asylum seekers relied more on social support and social networks to survive [11]. Another study that explored urban Congolese refugees' use of social capital to promote resilience during a period of political violence in Nairobi Kenya found out that, refugees used social capital across different contexts to access and distribute resilience-promoting resources [26].The above study observed that refugee women particularly relied on informal bonding forms of capital while men exhibited greater degrees of access to formal bridging and linking networks.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We also found that high levels of trust and solidarity were positively associated with quality of life with in our sample. Findings that the refugees depicted high levels of social capital are in line with a study, which found that asylum seekers relied more on social support and social networks to survive [11]. Another study that explored urban Congolese refugees' use of social capital to promote resilience during a period of political violence in Nairobi Kenya found out that, refugees used social capital across different contexts to access and distribute resilience-promoting resources [26].The above study observed that refugee women particularly relied on informal bonding forms of capital while men exhibited greater degrees of access to formal bridging and linking networks.…”
Section: Discussionsupporting
confidence: 85%
“…Yet existence of social capital among the refugees has been shown to reconstruct the lives of the refugees [9]. Studies on the relationship between social capital and quality of life have however recently gained popularity in biomedical and behavioral medicine [10,11]. Social capital theory is premised on the fact that the more the social capital (trust, networks, connections) within the community, the healthier the community would be [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] Additionally, analyzing individual-level data could enable incorporating a wider array of behavioral, social, and environmental factors that may influence mental health. [39,40,43,44] Future MR studies should integrate detailed measures of diet, physical activity, substance use, childhood experiences, and stress exposures. This will facilitate a more comprehensive understanding of the complex interrelationships between education, lifestyle, and psychiatric disease while accounting for confounding.…”
Section: Discussionmentioning
confidence: 99%